2010
DOI: 10.1515/jpem.2010.156
|View full text |Cite
|
Sign up to set email alerts
|

Kabuki Syndrome and Crohn Disease in a Child with Familial Hypocalciuric Hypercalcemia

Abstract: Background: Familial hypocalciuric hypercalcemia (FHH) results from a mutation of the calcium sensing receptor (CASR) gene and typically presents as asymptomatic hypercalcemia with inappropriately low urinary calcium excretion and normal or mildly elevated levels of parathyroid hormone. Objective: To describe a case of FHH associated with Kabuki syndrome and Crohn disease. Method: Genomic DNA was screened for CASR mutations and a retrospective chart review was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Future studies should be directed at the organismal and systemic levels in order to better define the net effect of the absence of the gene. In this respect, studies that characterize the phenotype of CaSR −∕− mice (Rey O et al, 2012 ; Macleod, 2013b ; Cheng et al, 2014 ) or associate SNPs in CaSR for diarrheal conditions (Ho et al, 2010 ; Romero et al, 2015 ) would be useful. Nonetheless, preliminary data from animals (Bovee-Oudenhoven et al, 1996 , 1997 ; Bovee Oudenhoven et al, 1997 , 1999 ) and clinical trials on humans (Bovee-Oudenhoven et al, 2003 ; Cheng et al, 2013 ; Dadu et al, 2015 ) using calcium or other CaSR ligands indicate that activation of this nutrient sensing receptor in vivo does reduce symptoms of infectious diarrheas (also see recent review by Cheng, 2016 ).…”
Section: Casr and Intestinal Absorption And Secretionmentioning
confidence: 99%
“…Future studies should be directed at the organismal and systemic levels in order to better define the net effect of the absence of the gene. In this respect, studies that characterize the phenotype of CaSR −∕− mice (Rey O et al, 2012 ; Macleod, 2013b ; Cheng et al, 2014 ) or associate SNPs in CaSR for diarrheal conditions (Ho et al, 2010 ; Romero et al, 2015 ) would be useful. Nonetheless, preliminary data from animals (Bovee-Oudenhoven et al, 1996 , 1997 ; Bovee Oudenhoven et al, 1997 , 1999 ) and clinical trials on humans (Bovee-Oudenhoven et al, 2003 ; Cheng et al, 2013 ; Dadu et al, 2015 ) using calcium or other CaSR ligands indicate that activation of this nutrient sensing receptor in vivo does reduce symptoms of infectious diarrheas (also see recent review by Cheng, 2016 ).…”
Section: Casr and Intestinal Absorption And Secretionmentioning
confidence: 99%
“…Previously described liver anomalies include biliary atresia, hepatic fibrosis, and sclerosing cholangitis 23) . Recently, a child with KS displayed inflammatory bowel disease 24) .…”
Section: Clinical Evaluation and Management Of Patients With Ksmentioning
confidence: 99%
“…Patients with KS might also display positive Coombs tests or a clinically overt autoimmune hemolytic anemia [34,45,47,50], autoimmune thyroiditis, and vitiligo [35,37,38,41,42,45,46,[49][50][51][52][53][54][55][56][57][58] (Table 1). In a mutational analysis referred to 12 Korean patients with KS, Cheon et al [19] reported one 51.8-month-old child with Hashimoto thyroiditis, though negative to the KMT2D mutation analysis.…”
Section: Immunol Resmentioning
confidence: 99%
“…Moreover, two cases of diabetes mellitus have also been reported in patients with KS [10,60], as well as one case of chorea with anti-phospholipid antibodies [46], arthritis [61], celiac disease [37], and Crohn's disease [53].…”
Section: Immunol Resmentioning
confidence: 99%